Agroecology sustainable ecosystem - Anand M. R.; Kommireddy, Poojitha; Seenappa C.; Ningaraju G. K. (CRC Press, an imprint of the Taylor & Francis Group, 2024)
Agroecology literacy is 'the degree to which people have an objective and well-informed understanding of crop production with environmental issues.' The increased food grain production has also increased the unscientific and indiscriminate use of agrochemicals which has affected the soil health and degraded agroecosystem adversely and brought down the immunity of soil and the productivity of crops. In addition, it has resulted in the over-exploitation of soil, leading to nutrient imbalance. Moreover, the negative impact of chemical agriculture on the environment and human health has been reported and documented. Increased environmental awareness and health consciousness promoted scientists and planners to think about sustainable farming practices as an alternate way for healthy agriculture to protect the environment and human health. Eco-friendly methods or ecosystem services are one solution to manage this issue. This book intends to provide the core elements of a curriculum for teaching agroecology at colleges and universities.--Provided by publisher.